The Effect of Role-Play and Brainstorming Technique on Students’ Speaking Achievement - Sihardo R. H. Simanjuntak; Erika Sinambela; Parlindungan Sach Lubis; Gusti Ayu Sri Andayani (Cetta: Jurnal Ilmu Pendidikan, 2019)
The objective of the study is to find out the significant effect of using Brainstorming technique and Role-Play technique on students’ speaking competence. In this research, the researcher used the experimental design. The population of this research was the ninth-grade students of SMP Negeri 1 Sunggal, Deli Serdang and the 60 of them were taken as the sample. The sample was obtained by random sampling technique. The data of the study were the studens’ score in speaking. The data of this study were obtained from the recording of students’ works which were transcribed onto students’ worksheets. The data were analyzed by t-test formula. The calculation showed that t-observed (8.19 by applying Brainstorming technique and 14.5 by applying Role-Play technique) is higher than t-table (1.671) at the level significance (0.05) and df (38). Alternative hypothesis (Ha) is accepted. It shows that teaching speaking by applying Brainstorming technique and Role-Play technique affected the students’ speaking achievement.